Assessment of Complications Caused by the Prescription-Free Consumption of Herbal Medicine with the Purpose of Weight Gain: A Case Report - Alireza Niknafs; Abbas Alimoradian; mehdi salehi (Tehran University of Medical Sciences, 2021)
In recent years, the common belief that herbal medications cause no side effects, have led to an increase in the consumption of these medications without prescription. Ginseng is one of the most commonly used herbs in the world and is a native of Eastern Asian countries such as China and Korea. It is also known to have several medicinal purposes. However, unreasonable use of this herb can bear consequences. In the current article, 28-year-old woman has consumed 4 capsules each day, which contained Ginseng roots, Alfalfa (Medicago sativa) extract, and Ziziphora  (Ziziphora capitate) extract  without a prescription to gain weight, which has resulted in serious side effects - including hepatotoxicity, psychologic, and gynecologic disorders. However, these symptoms were controlled with Chicory roots, Purslane and Jujube oxymel. PM focuses on the cooperation between food categories, nutritional instructions, food modulators, and medications. Regardless of their several therapeutic effects, medical herbs have been known to cause quite serious side effects if consumed unsystematically and without the surveillance of a doctor.